Investigating the language learning styles of Malaysian ESL learners: are the lecturers aware of these preferences? / Nurul Bazilah Abd. Hamid - Abd. Hamid, Nurul Bazilah (2011)
This research aimed to investigate the preferred language learning styles of pre-university ESL learners in Malaysia, as well as the extent to which the lecturers are aware of these preferences. A total of 136 learners were involved in this study, along with six language lecturers. A 13-item language learning preference questionnaire adopted from Brindley’s (1984) research was employed to elicit information from the respondents. The results obtained from the questionnaire revealed that an overwhelming number of learners preferred a more communicative type of learning, and appreciated being given the freedom to learn by listening and interacting with their fellow peers. They could also be categorized as being both auditory and visual learners. Moreover, the findings indicated that the lecturers were positively aware of the learners’ learning preferences in most instances. Therefore, it is highlighted that cooperation from lecturers and learners in identifying the latter’s preferred learning styles is imperative to ensure more beneficial learning outcomes.